Perancangan Antena Yagi Gain Tinggi Pada Ground Control Station Wahana Udara Nirawak - Melvi Melvi; Nur Fadillah; Yetti Yuniati; Aryanto Aryanto; Nora Aditiyan; Cahyo Mustiko Okta Muvianto; Ardian Ulvan (Jurnal Rekayasa Elektrika, 2020)
The uncrewed Aerial Vehicle (UAV) operation is currently dominated by autonomous technology (autopilot) rather than manual control via remote control. During flying the mission autonomously, communication between the UAV and the Ground Control Station (GCS) must be in good and stable conditions. The GCS can well receive the telemetry data and payload sensor data carried by the vehicle. Conversely, any inconsistency parameters can be corrected by the GCS before transmitted to the UAV. Therefore, the role of the antenna is crucial to avoid signal loss during the communication process. This study focuses on GCS’s antenna. By designing the Yagi type antenna with the optimization of the distance, the number of directors, material, and shape of the reflector through CST simulation. The best option chosen is the Yagi antenna with the same distance between directors, seven directors, copper material, and flat reflectors with a VSWR of 1.1134, return loss -25.411 dB and 10.7 dB of gain. The measurement result after fabrication is the VSWR of 2.165 and the return loss of -8.677 dB. The antenna test results, when the UAV was flown as far as 2.5 km, found that the signal strength received by the GCS is -70.68 dBm with RSSI 107, and the signal strength in percent is 96%.